Temporal Association in Hospitalizations for Tuberculosis, Invasive Pneumococcal Disease and Influenza Virus Illness in South African Children - Dangor, Ziyaad; Izu, Alane; Moore, David P.; Nunes, Marta C.; Solomon, Fatima; Beylis, Natalie; von Gottberg, Anne; McAnerney, Johanna M.; Madhi, Shabir A. (PloS one, 2014)
The seasonal variability in hospitalization for tuberculosis may in part relate to super-imposed bacterial or predisposing respiratory viral infections. We aimed to study the temporal association between hospitalization for culture-confirmed pulmonary tuberculosis (PTB), invasive pneumococcal disease (IPD) and influenza virus epidemics in South African children. We undertook a retrospective analysis which examined seasonal trends, from 2005 to 2008, for hospitalization for culture-confirmed PTB and IPD among children in relation to the influenza epidemics in Soweto, South Africa. Original time-series of the influenza virus epidemics and hospitalization rates for PTB and IPD were decomposed into three components: a trend cycle component, a seasonal component and an irregular component using the X-11 seasonal adjustment method. To compare the seasonality amongst the three series, the trend and irregular components were removed and only seasonal components examined. Across the study period, the influenza virus epidemics peaked during May to July (winter) months, which was closely followed by an increase in the incidence of hospitalization for IPD (August to October) and PTB (August to November). Within- and between-year temporal changes associated with childhood TB hospitalization may in part be driven by factors which influence temporal changes in pneumococcal disease, including potential variability in the severity of influenza virus epidemics in temperate climates. The dynamics of the interplay between the host and these infectious agents appears to be complex and multifactorial.